Botswana : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
Poverty and unemployment remained high in Botswana. The shortcomings of the labor market policies are responsible for a high unemployment rate. This selected issues paper sheds considerable light on ways that Botswana can enhance inclusive growth and reduce the high level of structural unemployment. Botswana was identified as having been able to sustain the highest economic growth compared with others in its league. Assessors suggest a prudent labor market for an overall sustained economic growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet